2010
DOI: 10.1016/j.antiviral.2009.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Novel approaches to inhibiting HIV-1 replication

Abstract: Considerable success has been achieved in the treatment of HIV-1 infection, and more than twodozen antiretroviral drugs are available targeting several distinct steps in the viral replication cycle. However, resistance to these compounds emerges readily, even in the context of combination therapy. Drug toxicity, adverse drug-drug interactions, and accompanying poor patient adherence can also lead to treatment failure. These considerations make continued development of novel antiretroviral therapeutics necessar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
102
0
7

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(111 citation statements)
references
References 352 publications
(517 reference statements)
2
102
0
7
Order By: Relevance
“…These include nucleoside 2 and non-nucleoside 3 inhibitors of reverse transcriptase (RT), inhibtors of HIV protease, 4 strand transfer inhibitors of integrase (IN), 5,6 chemokine receptor 5 (CCR5) antagonists, and HIV entry inhibitors, 7 all of which have marketed drugs available to patients. Additionally, a number of investigational mechanisms of action have been identified, 8 including noncatalytic site integrase inhibitors (NCINIs), first disclosed in 2007. 9 Recent work has shown that this class of inhibitor binds to an allosteric pocket on the catalytic core domain (CCD) of IN, shifting the oligomerization equilibrium of IN toward the tetrameric state.…”
mentioning
confidence: 99%
“…These include nucleoside 2 and non-nucleoside 3 inhibitors of reverse transcriptase (RT), inhibtors of HIV protease, 4 strand transfer inhibitors of integrase (IN), 5,6 chemokine receptor 5 (CCR5) antagonists, and HIV entry inhibitors, 7 all of which have marketed drugs available to patients. Additionally, a number of investigational mechanisms of action have been identified, 8 including noncatalytic site integrase inhibitors (NCINIs), first disclosed in 2007. 9 Recent work has shown that this class of inhibitor binds to an allosteric pocket on the catalytic core domain (CCD) of IN, shifting the oligomerization equilibrium of IN toward the tetrameric state.…”
mentioning
confidence: 99%
“…В зависимости от механизма действия противовирусные препараты делятся на классы, включающие ингибиторы обратной транскриптазы (нуклеозидные, ненуклеозидные и нуклеотидные), протеазы, интегразы, а также ингибиторы проникновения (слияния) [10][11][12][13][14][15]. Совместное использование этих препаратов формирует основу для высокоактивной антиретровирусной терапии (ВААРТ), которая значительно повысила выживаемость многих пациентов, инфицированных ВИЧ [16].…”
Section: Introductionunclassified
“…This technique is currently used for treatment of symptomatic uterine fibroids [23] and hepatocellular tumors [24] . The standard protocol for evaluation of this intervention consists of dynamic gadolinium-enhanced 3D pelvic MR angiography and delayed contrast enhanced MRI [25] .…”
Section: Body Interventionsmentioning
confidence: 99%
“…Assessment of embolization relies on interpretation of visual blood flow information [23,31] and operator inferences. The limitations of transcatheter arterial embolization were demonstrated in a study probing the perceived and real completeness of uterine fibroid embolization.…”
Section: Body Interventionsmentioning
confidence: 99%